Aesthetic Acculturation of the Architectural Style of the Baiturrahman Grand Mosque as a Key Identity of Acehnese Culture - binti Ismaizam , Nur Rusyda Hannah (Universitas Islam Raden Rahmat Malang, 2023)
Baiturrahman Grand Mosque of Aceh is one of the mosques that existed in Southeast Asia. It is very old compared to other mosques which indicated that this mosque had been through a lot for a long time. Besides, the discussion can cover many areas even from its foundation until its utilization. As for the history, the mosque had adopted its designs from outside since the Dutch’s intervention until the present. This then raises a problem of unfamiliarity for the locals in recognizing themselves to the particular mosque. Therefore, this study is aimed to investigate the benefit that Acehnese gets in terms of the identity from the mixed architecture style of the mosque. Furthermore, to achieve this aim, this thesis applies historical methodology and in a descriptive way. Also library research that prioritizes the secondary sources such as journal articles, books, websites and others, are included. As a result, the Baiturrahman Grand Mosque still holds the identity of the locals in its architecture despite the practice of eclecticism. With that being said, this research can bring a new context about the mosque. The education about the mosque can be emphasized which makes people feel more obligated to take care of the building. It is then expected for this research to be one of the sources for any topics that are related with the mosque.